PHONOLOGICAL INTEGRATION OF MINANGKABAU LANGUAGE WITH BENGKULU MALAY LANGUAGE IN THE LYRICS OF THE BENGKULU LOCAL SONG “IKAN PAIS” - Harmia, Citra Dewi (Kantor Bahasa Maluku Utara, 2024)
This article aims to describe the phenomenon of phonological integration of the Minangkabau language in Bengkulu Malay which is contained in the lyrics of the Bengkulu’s traditional song entitled